Step-by-step explanation:





If you graph the new identity, and the og identiy, they will be conciding graphs, so they are the same identity.
Answer:
Jenny is wrong the correct answer is x²+ 4 - 4 x.
Step-by-step explanation:
Given that
(x-2)³∕x-2
(x-2)³∕(x-2) =(x-2) (x-2)²∕(x-2)
(x-2)³∕(x-2) = (x-2)²
As we know that
(a-b)² = a²+b² - 2 ab
So
(x-2)² = x²+ 2² - 2 ˣ 2 ˣ x = x²+ 4 - 4 x
(x-2)² = x²+ 4 - 4 x
It means that
(x-2)³∕(x-2) = (x-2)² = x²+ 4 - 4 x
So Jenny is wrong the correct answer is x²+ 4 - 4 x.
Answer:
what solid figure do u have a picture lol?
Step-by-step explanation: